The fraction of CD117/c‐KIT‐expressing erythroid precursors predicts ESA response in low‐risk myelodysplastic syndromes. Issue 3 (9th April 2019) - Raimbault, Anna; Itzykson, Raphael; Willems, Lise; Rousseau, Alice; Chapuis, Nicolas; Mathis, Stéphanie; Clauser, Sylvain; Radford‐Weiss, Isabelle; Bouscary, Didier; Fontenay, Michaela; Kosmider, Olivier; Bardet, Valérie
Abstract : Background: Compelling evidence has emerged for the relevance of flow cytometry (FC) in the diagnostic work‐up of myelodysplastic syndromes (MDS) but due to technical issues, the erythroid lineage has been under investigated, specifically in the therapeutic context. Methods: Using the "no red cell lysis" method developed to set up the RED‐score, we specifically quantified the fraction of CD117/c‐KIT‐expressing erythroid precursors in a cohort of 144 MDS patients and studied the correlation with response to erythropoiesis‐stimulating agents (ESA) in a sub cohort of 63 low‐risk MDS patients. Results: We confirmed the previously reported increase in CD117/c‐KIT‐expressing erythroid precursors in a subset of MDS patients and demonstrated a strong association between a cut off of CD117/c‐KIT‐expressing erythroid precursors ≥3% and ESA response ( P = 0.001), independent of red blood cell requirement. From our observations, we hypothesized that a decrease in CD117/c‐KIT‐expressing erythroid precursors could be a mechanism of ESA failure. Moreover, the fraction of CD117/c‐KIT‐expressing erythroid precursors was correlated with progression‐free survival in low‐risk MDS patients ( P = 0.018). In vitro, we demonstrated in an EPO dependent cell line that CD117/c‐KIT expression is necessary for cell survival under EPO stimulation. Conclusions: The quantification of the CD117/c‐KIT‐expressing erythroid precursors could be proposed as a new theranostic and prognostic marker in MDS treated by ESA. Future studies will be required to determine whether modulating CD117/c‐KIT expression and signaling could be used to improve anemia in MDS. © 2019 International Clinical Cytometry Society